The God I love : a lifetime of walking with Jesus - Tada, Joni Eareckson (Grand Rapids, Mich. : Zondervan, 2003)
"More than three decades ago, a diving accident left Joni Eareckson Tada a quadriplegic. Back then she questioned how a loving God could condemn an active young woman to a life in a wheelchair. Today she is grateful. Because it's from this vantage point that Joni has discovered a God who is so magnificent that no circumstance, no matter how terrible, can separate her--or you--from his fierce, tender, and enduring love"--Jacket.
Includes bibliographical references.
Keywords: Tada, Joni Eareckson; Christian biography -- United States